The Role of Brand Ambassador, Event Marketing and Digital Marketing on Purchase Decisions User Shopee - William Kok; Yeni Ariesa; Kelvin Kelvin; Vincent Pratama; Steven Kosasih; Vedas Fernand Alianza (Budapest International Research and Critics University, 2021)
Study this aim to test and analyze the influence of the role of brand ambassadors, event marketing and digital marketing on the purchasing decisions of shopee users. The type of research isafdquantitative by number of samples research that is 100 consumers. The conclusion from the results of this study is the results of the Latent Variable 1 hypothesis test, namely the brand ambassador has a path coefficient value of 0.525 and a p-value of 0.000 <0.05 so that the hypothesis is accepted or fragmented by positive and significant dominance. The results of the Latent Variable 2 hypothesis test that event marketing has a path coefficient value of 0.280 and a p-value of 0.003 <0.05 so that it partially has a positive effect. The results of the Latent Variable 3 hypothesis test, namely digital marketing has a path coefficient value of 0.141 with a p-value of 0.157> 0.05 and a t-statistic of 1.418 so that fragmentation does not have a positive effect on purchasing decisions.